Association between carotid artery diameter and aortic aneurysm - Yamaguchi, Takenori; Yasaka, Masahiro; Ogata, Toshiyasu; Nagatsuka, Kazuyuki; Minematsu, Kazuo (Nihon Rōnen Igakkai zasshi, 2002)
Although it has been suggested that an increase in arterial diameter is related to atherosclerotic risk factors, there are only a few reports about the relationship between the diameter of the common carotid artery (CCA) and the presence of aortic aneurysm (AA). We measured CCA diameters by carotid ultrasonography in 132 consecutive AA patients over 40 years of age (aneurysm group), and in 414 consecutive subjects over 40 years of age without AA (control group). We also studied the size of AA based on CT, MRA or surgical findings. We compared CCA diameters with atherosclerotic risk factors between the two groups, and studied the relationship between the CCA diameters and AA size by types of aneurysm. In the aneurysm group, men (85% vs 69%, p<0.001), hypertension (88% vs 67%, p<0.001) and smoking (63% vs 46%, p<0.001) were more frequent, and the diameter of the CCA (right, 7.0±1.1mm vs 6.3±1.0mm, p<0.001; left, 6.7±1.1mm vs 6.1±1.0 mm, p<0.001) was significantly larger than those in the control group. Multiple logistic regression analysis indicated that dilatation of CCA on either side was a significant risk factor for AA (right, odds ratio 1.69, p<0.001, left, odds ratio 1.48, p<0.001) as well as hypertension and smoking. There were no differences in size of the CCA according to the site of aneurysm. However the CCA diameter was significantly related to the size of the thoracic AA (r=0.350, p<0.05 for the right CCA) and dissecting AA (r=0.506, p<0.05 for the left CCA). In conclusion, the increase in CCA diameter may suggest the presence of AA, and CCA diameter appears to be related to AA size.